The important of control environment and its implementation by selected Malaysian public universities in preventing fraud - Abdul Kadir, Dzarfan; Ahmad, Adura; Md Yusof, Mohd 'Atef; Othman, Zaleha (Universiti Utara Malaysia, 2009)
This study intend to gain insights on selected public universities’ perceptions on control environment as fraud prevention tools and their implementation in the organization based on suggestion by Committee of Sponsoring Organization of the Treadway Commission (COSO), Internal Control Integrated Framework (1992). The results reveal that both UUM and UNIMAP view highly on the importance of control environment in preventing fraud. Both teams of university’s management aware that the five components of the control environment need to be implement especially code of ethics.Unfortunately, this study found that lack of internal audit staff especially faced by UNIMAP lead to their inability to perform pro-active auditing which is part of monitoring components in control environment.The results of this study could assist management to impose better system fraud detection.